The Meanest Hound Around - Wallace, Carol, 1948-; Wallace, Bill (New York : Simon & Schuster Books for Young Readers, 2003)
After being abandoned, Freddie helps a mild-tempered dog named Spike escape from a cruel junkjard owner and the two manage to survive on their own until they find a loving home.
Keywords: Dogs -- Fiction